1998
DOI: 10.1103/physreva.57.4616
|View full text |Cite
|
Sign up to set email alerts
|

Observation of oscillations between degenerate bound-state configurations in rapidly autoionizing two-electron atoms

Abstract: The oscillation between bound-state configurations in a rapidly autoionizing three-body Coulomb system has been directly observed. Using a 500-fsec laser pulse, calcium atoms are excited to the pure 4p 3/2 15d twoelectron configuration at an energy greater than 3 eV above the ionization limit. As a result of configuration interaction, the electrons scatter coherently into multiple bound and continuum configurations. The oscillation between the degenerate 4p 1/2 n�d and 4p 3/2 nd modes as well as autoionization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
16
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…At the temporal resolution of the experiment, high-frequency Ramsey fringes corresponding to the excitation frequencies of each AIS are averaged out and the low-frequency components of the evolution of the coherent superposition dominate the trace 22 . Contributions from modulations in the excitation process due to the two interfering wave packets are not to be excluded 23,24 . Fourier transform (FT) of the traces reveals frequency differences of the excited states (Fig.…”
mentioning
confidence: 99%
“…At the temporal resolution of the experiment, high-frequency Ramsey fringes corresponding to the excitation frequencies of each AIS are averaged out and the low-frequency components of the evolution of the coherent superposition dominate the trace 22 . Contributions from modulations in the excitation process due to the two interfering wave packets are not to be excluded 23,24 . Fourier transform (FT) of the traces reveals frequency differences of the excited states (Fig.…”
mentioning
confidence: 99%
“…Dynamics of wave packets in this two-electron system have also been studied [15]. Some effects of oscillating bound configurations on wave packet behavior have been observed [16]. Quantum measurement studies have also been performed using a perturbative ICE [17].…”
mentioning
confidence: 98%
“…The evolution of wave packets is highly dependent on the spacing between states, making Stark states an excellent system in which to study temporal dynamics, since the evolution of the wave packets can be controlled by simply changing the size of the applied electric field. The use of Rydberg wave packets in the study of doubly excited atoms has been shown to be a useful tool for studying the dynamical interaction between the two excited electrons [10][11][12][13][14][15][16][17][18][19][20]. The use of applied electric fields to control the evolution of the two electron wave packets provides a sensitive tool in the study of the interelectron interaction.…”
mentioning
confidence: 99%